The importance of cohesion policy for the development of the railway system of the Republic of Croatia - Lukin, Dorotea (Array, 2021)
Cohesion policy is one of the European Union’s policies, which provides Member States with the possibility of financial support under the European Structural and Investment Funds (ESI Funds) as well as with the Connecting Europe Facility (CEF), to reduce disparities and encourage the development of less developed Member States. By funding through Cohesion policy funds, the European Union seeks to accomplish a prosperous economy by achieving appropriate European standards in the individual Member States. Cohesion policy emphasizes the development of transport and mobility, and in particular, the investment in key transport links and sections of international importance through the revitalization of railway infrastructure in line with European Union standards. The railway system of the Republic of Croatia has been under-invested for many years, which is why it has not followed the requirements and needs of the development of the transport market. Membership in the European Union has provided the Republic of Croatia with co-financing for the development of the railway system. This paper will analyse the current investments in the railway system and the development potentials that are planned to be achieved in the next programming period. Therefore, the purpose of this paper is to analyse the importance of the Cohesion Policy of the European Union for the development of the railway system of the Republic of Croatia in the Programming period 2021-2027. The analysis aims to identify opportunities for further development of the railway system as the ‘cleanest’ transport industry, guided by the need to reduce harmful emissions following the European Green Deal by using funds from the European Structural and Investment Funds.